2012
DOI: 10.1021/je300487n
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties of Five Acetate-Based Ionic Liquids

Abstract: Ionic liquids (ILs) with improved hydrogen-bonding acceptor abilities, such as acetate-based compounds, have shown great potential for CO 2 capture and biomass dissolution. In this context, the knowledge of the thermophysical properties of acetate-based fluids is essential for the design and scale-up of related processes. However, at this stage, acetate-based ILs are still poorly characterized. In this work, four thermophysical properties, specifically, density, viscosity, refractive index, and surface tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
99
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(118 citation statements)
references
References 60 publications
(161 reference statements)
15
99
2
Order By: Relevance
“…As previously observed for other ILs [6,31,[34][35][36]57], imidazolium-based fluids combined with cyanobased anions display low surface enthalpies and entropies when compared with molecular organic compounds. This low surface enthalpies and entropy reflect a high surface organization as well as a highly structured liquid phase.…”
Section: Surface Thermodynamics Properties and Estimated Critical Temsupporting
confidence: 77%
See 2 more Smart Citations
“…As previously observed for other ILs [6,31,[34][35][36]57], imidazolium-based fluids combined with cyanobased anions display low surface enthalpies and entropies when compared with molecular organic compounds. This low surface enthalpies and entropy reflect a high surface organization as well as a highly structured liquid phase.…”
Section: Surface Thermodynamics Properties and Estimated Critical Temsupporting
confidence: 77%
“…As reported in previous works [6,31,[34][35][36]57], the values for critical temperatures of ILs obtained by these approximations must be used with caution. The estimation of critical temperatures using data from a narrow temperature range, and demanding a large extrapolation, are a source of uncertainty.…”
Section: Surface Thermodynamics Properties and Estimated Critical Temmentioning
confidence: 89%
See 1 more Smart Citation
“…Coutinho et al [20,[24][25][26][27][28][29][30][31][32] found that surface tension in a couple of imidazolium-based IL series decreases with an increase in the cation side alkyl chain length up to hexyl and thus defined the CACL (critical alkyl chain length). On the other hand, surface tension remained almost constant for ILs with aliphatic moieties longer than the obtained CACL.…”
mentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Once more, a multivariate correlation with several quantum chemistry descriptors along with temperature as input parameters, and ln (viscosity), as the output parameter, was developed using Eureqa software.…”
Section: Viscositymentioning
confidence: 99%